UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS BPR DI KABUPATEN TANGERANG - Gabriela Melina Widiasih; Agung Dharmawan Buchdadi; Muhammad Yusuf (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the effect of liquidity and solvency on profitability with company size as a moderator in BPRs in Tangerang Regency registered with the Financial Services Authority (OJK) for the period 2019 - 2022. The independent variables in this research are cash ratio (CR) proxy liquidity and solvency. Capital Adequacy Ratio (CAR) proxy. The dependent variable used in this research is the profitability proxy Return on Assets (ROA) and the moderating variable, namely company size. The number of bank samples used was 13 companies and the observation period was four years so that 52 observation objects were selected for analysis. Sampling in this study used a purposive sampling method. The results of this research indicate that liquidity has a significant negative effect on profitability. Solvency has a significant negative effect on profitability. Company size is unable to moderate the effect of liquidity on profitability. Company size is able to moderate the influence of solvency on profitability. This research is expected to add to the literature on the influence of liquidity and solvency on profitability and provide more information to depositors to consider liquidity and solvency before placing funds in a BPR. This research also has several limitations, namely that the use of samples is only limited to the district scope